The analysis of entrepreneurship course towards entrepreneurship intention of the students - Charly Hongdiyanto (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2021)
This research purpose is to analyze the development of entrepreneurship intention of the student through entrepreneurship course. The research subjects are the students, the lecturers of Entrepreneurship course and the coordinator of Entrepreneurship Course in Ciputra University. The research uses qualitative descriptive study. This research result shows that the development of entrepreneurship intention of the student through entrepreneurship course in Ciputra University is different between one to another. It depends on the student him/herself. Ciputra University already used and gives the best method to facilitate the students, but students who want to learn more about entrepreneurship is the one that can develop their entrepreneurship intention.